Pengaruh Minyak Nabati Sebagai Pendingin Terhadap Temperatur dan Kekasaran Permukaan Baja ST 42 pada Proses Pembubutan - Rangkuti, Mhd. Saleh; Aljufri, Aljufri; Rizki, Muhammad Nuzan; Rahman, Abdul; Muhammad, Muhammad (Malikussaleh Journal of Mechanical Science and Technology, 2024)
In the machining process, selecting the appropriate tool and coolant significantly affects the surface roughness of a product to be manufactured. The purpose of this research is to compare between soluble oil and vegetable oil as coolants in reducing roughness values and dissipating heat generated during the machining process of ST 42 steel. Carbide tools and vegetable oil coolants, namely cooking oil and castor oil, are used in this study, with soluble oil used as a reference. The machining process in this study employs conventional machining with a spindle speed of 1200 rpm, a cutting depth of 0.2 mm and 0.4 mm, and a cutting speed of 0.04 mm/minute. Temperature data collection during the machining process is carried out using a thermogun, and surface roughness testing is conducted using a Mitutoyo SJ-310 surface roughness tester. From the test results, the lowest roughness and temperature values are obtained at a cutting depth of 0.2 mm for all types of coolants used. The use of soluble oil yields the lowest average roughness and temperature values, which are 35.2 °C and 0.9 µm, respectively. Meanwhile, in the use of vegetable oil to minimize surface roughness, the lowest average value is found in cooking oil, which is 1.5 µm, and to minimize surface temperature during machining, castor oil coolant is the most effective, with a temperature of 40.1 °C.